2017
DOI: 10.1002/eji.201746964
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus vector expressing RAE‐1γ induces enhanced anti‐tumor capacity of murine CD8+ T cells

Abstract: Designing of CD8 T cell vaccines which would provide protection against tumors is still considered a great challenge in immunotherapy. Here we show a robust potential of a cytomegalovirus (CMV) vector expressing the NKG2D ligand RAE-1γ as CD8 T cell-based vaccine against malignant tumors. Immunization with the CMV vector expressing RAE-1γ delayed tumor growth or even provided complete protection against tumor challenge in both prophylactic and therapeutic settings. Moreover, a potent tumor control in mice vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 53 publications
(77 reference statements)
0
25
0
6
Order By: Relevance
“…However, additional approaches will be necessary to develop a HCMV vaccine which will be efficient against congenital infection. We have already shown in MCMV model that by exploiting viral immunoevasins one can generate highly attenuated vaccine vectors which are at the same time able to induce potent cellular immunity (Slavuljica et al, 2010, Trsan et al, 2013, Trsan et al, 2017). One important question that remains unanswered is whether CMV evades the development of more efficient antibody response.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional approaches will be necessary to develop a HCMV vaccine which will be efficient against congenital infection. We have already shown in MCMV model that by exploiting viral immunoevasins one can generate highly attenuated vaccine vectors which are at the same time able to induce potent cellular immunity (Slavuljica et al, 2010, Trsan et al, 2013, Trsan et al, 2017). One important question that remains unanswered is whether CMV evades the development of more efficient antibody response.…”
Section: Discussionmentioning
confidence: 99%
“…CD8 to considered as glycoprotein heterodimer made up of alpha and beta chains covalently linked by a disulfide bond. The function of CD8 is to bind to a major histocompatibility complex class I molecule associated with the T cell receptor and stimulate its cytotoxic effect on cancer cells and induce a vital role in cell-mediated immunity [ 23 ]. Although many studies have shown patients with higher intra-tumor CD8 + TILs have superior survival in many malignancies [ 24 26 ], there was no significant difference in prognosis observed within our study probably due to the limited sample size used.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, this response was also preserved in NKG2D −/− mice, suggesting an NKG2D-independent immune function of RAE-1γ [28]. Consequently, a RAE-1γMCMV vector expressing the SIINFEKL epitope induced a robust CD8 T cell response able to contain the growth of an OVA-expressing tumour in prophylactic and therapeutic settings [48]. Therapeutic RAE-1γMCMV vaccination was further enhanced by blocking the immune checkpoints TIGIT and PD-1, supporting a synergistic role with tumour immunotherapy.…”
Section: Innate Immune Response To CMV Is Relevant For Its Vector Promentioning
confidence: 90%
“…Therefore, it is imperative for any HCMV vaccine vector to be attenuated. The generation of replication deficient CMVs that maintain their immunogenicity [36,44] and the modification of genome portions that contain evasions genes [45], as well as the insertion of activating ligands to increase immune control of CMV [46][47][48] are strategies that will be described in this review. Interestingly, a replication-deficient MCMV carrying an attenuating mutation within the DNA primase gene, while able to induce primary T cell responses could not replicate the characteristic MI CD8 response [49].…”
mentioning
confidence: 99%